Pengembangan Potensi Desa Wisata Berbasis Ekonomi Kreatif untuk Meningkatkan Perekonomian Masyarakat - Gratia Wirata Laksmi; Tarigan, Emenina; Dewi, Triana Rosalina; Ingkadijaya, Rahmat (LPPPM STAI Darul Hikmah Bangkalan, 2024)
Dusun Sambirejo and Dusun Tapansari, located in Desa Watusigar, Ngawen Subdistrict, Gunung Kidul Regency, Central Java, hold considerable untapped creative economic potential, particularly in the tourism sector. This potential stems from the area's natural beauty, cultural traditions, and unique local products such as traditional hats, soy milk, horticultural snacks, recycled crafts, and herbal medicine. However, several challenges have been identified, including limited community skills in producing creative products, lack of knowledge regarding effective packaging techniques, and restricted market access. The goal of this community service activity is to strengthen the entrepreneurial capacity of the community through creative economy initiatives in both villages. The method employed is a participatory ethnographic approach, which provides an in-depth understanding of the social and cultural environment of the target community. The results of this initiative indicate a high potential for developing a creative economy based on the area's natural and cultural wealth. This potential can be optimized through innovations in attractive and environmentally friendly packaging, improvements in production efficiency, and broader marketing strategies, including digital marketing. These innovations are expected to enhance the economic value of local products, expand market access, and significantly contribute to the economic improvement of the community at both regional and national levels